Surface speciation of phosphate on goethite as seen by InfraRed Surface Titrations (IRST) - Arroyave Rodriguez, Jeison Manuel (2018)
Phosphate adsorption at the metal oxide-water interface has been intensely studied, and the system phosphate-goethite in aqueous media is normally used as a model system with abundant information regarding adsorption-desorption under very different conditions. In spite of this, there is still discussion on whether the main inner-sphere surface complexes that phosphate forms on goethite are monodentate or bidentate. A new spectroscopic technique, InfraRed Surface Titration (IRST), is presented here and used to systematically explore the surface speciation of phosphate on goethite in the pH range 4.5–9.5 at different surface coverages. IRST enabled to construct distribution curves of surface species and distribution curves of dissolved phosphate species. In combination with the CD-MUSIC surface complexation model it was possible to conclude that surface complexes are monodentate. Very accurate distribution curves were obtained, showing a crossing point at pH 5.5 at a surface coverage of 2.0 μmol m−2, with a mononuclear monoprotonated species predominating at pH > 5.5 and a mononuclear diprotonated species prevailing at pH < 5.5. On the contrary, at the low surface coverage of 0.7 μmol m−2 there is no crossing point, with the mononuclear monoprotonated species prevailing at all pH. IRST can become a powerful technique to investigate structure, properties and reactions of any IR-active surface complex at the solid-water interface.